Expression of nat05 encoding for a nattokinase in Bacillus subtilis BD170 - Thư, Nguyễn Thị Anh; Trang, Hồ Thị (Hue University Journal of Science: Natural Science, 2021)
Nattokinase, a serine protease found in the Japanese Natto product, can specifically dissolve fibrin fibers causing coagulation and is useful in endogenous thrombolysis. Currently, nattokinase is produced with the help of traditional fermentation and recombinant DNA technology approaches. In this study, we presents the optimization of time and the inducing substance (IPTG) concentration of gene nat05 encoding for a nattokinase in Bacillus subtilis BD170 with strong protease activity. After 10 hours’ cultivation, nat05 expresses 9.5 times higher than the control. At the IPTG concentration of 2 mM, nat05 exhibits the strongest activity, which is 10 times higher than the control.